Ultrafast magnetodynamics with free-electron lasers. (9th January 2018) - Malvestuto, Marco; Ciprian, Roberta; Caretta, Antonio; Casarin, Barbara; Parmigiani, Fulvio
Abstract: The study of ultrafast magnetodynamics has entered a new era thanks to the groundbreaking technological advances in free-electron laser (FEL) light sources. The advent of these light sources has made possible unprecedented experimental schemes for time-resolved x-ray magneto-optic spectroscopies, which are now paving the road for exploring the ultimate limits of out-of-equilibrium magnetic phenomena. In particular, these studies will provide insights into elementary mechanisms governing spin and orbital dynamics, therefore contributing to the development of ultrafast devices for relevant magnetic technologies. This topical review focuses on recent advancement in the study of non-equilibrium magnetic phenomena from the perspective of time-resolved extreme ultra violet (EUV) and soft x-ray spectroscopies at FELs with highlights of some important experimental results.